Better Sexy than Flexy? A Lab Experiment Assessing the Impact of Perceived Attractiveness and Personality Traits on Hiring Decisions - Stijn Baert; Lynn Decuypere (Institute for the Study of Labor (IZA), 2013)
In this letter we present a laboratory experiment to assess the relative and independent effect of perceived attractiveness and personality traits on hiring decisions. Our results indicate that attractiveness and conscientiousness, followed by emotional stability, are important drivers of recruiters' decisions.
Keywords: C91; J24; J71; 330; lab experiments; hiring discrimination; economics of beauty; economics of personality